INVERSE HEAT CONDUCTION PROBLEM IN A SOLID SPHERE AND ITS THERMAL STRESSES - KEDAR, GANESH; Pawar, S.P; Deshmukh, K.C (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper discusses the solution of an inverse heat conduction problem of one dimensional temperature distribution and stress field for a solid sphere. The sphere is subjected to arbitrary temperature within it under unsteady state condition. Initially the sphere is maintained at constant temperature. The governing heat conduction equation has been solved by the integral transform technique. The temperature distribution,unknown temperature and thermal stresses are obtained in the form of trigonometric function. The numerical example is presented for Titanium alloy to discuss the results.